Współczesny nauczyciel w przestrzeni technologii informacyjnych = The contemporary teacher in the area of information technologies - Szempruch, Jolanta (Zielona Góra: Lubuskie Towarzystwo Naukowe)
The dynamic development of new production techniques, of storage, processing, and transmission of information (which naturally leads to social, economic, and cultural changes) has also impact on the functioning of the educational system and the teacher?s work. Information and communication technologies are becoming a basic element of the development of information society. Schools of every level are undergoing an intensive process of electronization and digitalization of the education process. Also, work on electronization and digitalization of textbooks and didactic materials is in progress. Library functions and tools, education models, and didactic methods are changing.
Keywords: nauczyciele; cyberkultura; technologie informacyjne; społeczeństwo informacyjne; wyzwania edukacyjne; komunikowanie się; kompetencje; teacher; cyberculture; information technologies; information society; educational